2021
DOI: 10.3126/irjms.v5i1.35870
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting Practices on Organizational Performance Mediated by Rationalized Managerial Decisions

Abstract: The study aimed to examine the influence of management accounting practices on organizational performance with the mediating effect of rationalizing managerial decisions of the Nepalese listed manufacturing companies. It is based on survey data from 221 respondents from the seven listed manufacturing companies, whose shares are traded regularly in Nepal's secondary market. The data were analyzed using confirmatory factor analysis, path analysis, and structural equation modeling to dissect and decipher details.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Bikhchandani and Sharma (2001) highlight its prevalence in emerging markets, where weak reporting requirements and lower accounting standards escalate information cascades and reputational herding. This resonates with findings by Dahal et al (2020) showing no significant impact of management accounting practices on organizational performance in the Nepalese context. Yong (2011) demonstrates the impact of the winner's curse hypothesis and the bandwagon effect on IPO initial returns in Malaysia, underscoring the influence of informed investor participation on stock performance.…”
Section: Bandwagon Effectsupporting
confidence: 84%
“…Bikhchandani and Sharma (2001) highlight its prevalence in emerging markets, where weak reporting requirements and lower accounting standards escalate information cascades and reputational herding. This resonates with findings by Dahal et al (2020) showing no significant impact of management accounting practices on organizational performance in the Nepalese context. Yong (2011) demonstrates the impact of the winner's curse hypothesis and the bandwagon effect on IPO initial returns in Malaysia, underscoring the influence of informed investor participation on stock performance.…”
Section: Bandwagon Effectsupporting
confidence: 84%
“…Field and Lowry (2009) showed that institutional investments in firms going public showcase the impact of institutions on shaping market dynamics. Nilsson's (2008) examined on retail socially responsible investment (SRI) in mutual funds brings an ethical dimension, suggesting investors consider social responsibility with rationalized decision-making (Dahal et al, 2020). Mateev and Videy (2008) explored the association between macroeconomics and capital markets in transition economies provide a contrasting perspective on the relationship between macroeconomic factors and stock returns.…”
Section: Original Research Articlementioning
confidence: 99%
“…The focus of international banks has changed from conventional to non-conventional revenue sources, aiming to boost profitability with enhanced earnings per share and dividend payout to their shareholders amidst intense competition, which leads to improved stock market performance (Karki, 2018). Deregulation, globalization, and technological advancements have been key drivers behind this shift (Craigwell & Maxwell, 2006;Dahal et al, 2020). Non-interest income now constitutes a substantial portion of operating revenue for US commercial banks (DeYoung & Rice, 2004).…”
Section: Introductionmentioning
confidence: 99%